2021
DOI: 10.3390/en14071941
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Construction Product Assessment Issues and Sustainability among Investors, Architects, Contractors, and Sellers of Construction Products in Poland

Abstract: The building sector is one of the most critical branches of the economy influencing global warming today. Following the European Union’s Construction Products Regulation (CPR), the sustainable use of natural resources in construction is one of the seven basic buildings’ requirements. However, due to the lack of provisions in this regard, construction products are not yet subject to mandatory assessment and verification of the constancy of performance in this area. The paper presents the research results with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
(37 reference statements)
1
15
0
2
Order By: Relevance
“…The authors conducted a survey among construction experts from Northern Poland to detect their subjective perspectives about risk costs and analyze the corresponding costs structure for the investment in sustainable projects. The issue of integrating sustainability into construction projects was studied by Michalak and Michalowski [94], who conducted a survey among 842 respondents who were investors, architects, contractors, and building-material vendors. The survey was designed to illustrate their perception of the issues related to the concept of sustainable development and their knowledge of selected documents applicable in the construction industry.…”
mentioning
confidence: 99%
“…The authors conducted a survey among construction experts from Northern Poland to detect their subjective perspectives about risk costs and analyze the corresponding costs structure for the investment in sustainable projects. The issue of integrating sustainability into construction projects was studied by Michalak and Michalowski [94], who conducted a survey among 842 respondents who were investors, architects, contractors, and building-material vendors. The survey was designed to illustrate their perception of the issues related to the concept of sustainable development and their knowledge of selected documents applicable in the construction industry.…”
mentioning
confidence: 99%
“…Officially, in the implementation report of 2016, the Commission [25] confirmed that national authorities and other stakeholders had already made legislative and administrative efforts both to ensure proper implementation of the CPR. Practically in most of the Member States inclusion of CPR into the national legal system was executed at least through a direct reference to Regulation 305/2011 and its application for construction products covered by hEN or ETA issued for them (e.g., "products covered by hEN or covered by ETA must be placed on the market in accordance with the Regulation (EU) No 305/2011") [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…[53,54] Nowadays, such an approach becomes important in light of the global transformation toward sustainable construction and the circular economy. [55,56] An analysis of the obtained LCA results, in light of the authors' previous papers, proves that the proper selection of laboratory is a key factor determining the environmental characteristics of the process. For Al 2 O 3 and ZrO 2 composites produced with the CSC method, the power demand to make one sinter amounts to ca.…”
Section: Characteristics Of Specimens Formed By Centrifugal Slip Castingmentioning
confidence: 91%